Efficacy and acceptability of a home-based, family-inclusive intervention for veterans with TBI: A randomized controlled trial. (20th March 2016) - Winter, Laraine; Moriarty, Helene J.; Robinson, Keith; Piersol, Catherine V.; Vause-Earland, Tracey; Newhart, Brian; Iacovone, Delores Blazer; Hodgson, Nancy; Gitlin, Laura N.
Abstract: Objective : Traumatic brain injury (TBI) often undermines community re-integration, impairs functioning and produces other symptoms. This study tested an innovative programme for veterans with TBI, the Veterans' In-home Programme (VIP), delivered in veterans' homes, involving a family member and targeting the environment (social and physical) to promote community re-integration, mitigate difficulty with the most troubling TBI symptoms and facilitate daily functioning. Setting : Interviews and intervention sessions were conducted in homes or by telephone. Participants : Eighty-one veterans with TBI at a VA polytrauma programme and a key family member. Design : This was a 2-group randomized controlled trial. Control-group participants received usual-care enhanced by two attention-control telephone calls. Follow-up interviews occurred up to 4 months after baseline interview. Main measures : VIP's efficacy was evaluated using measures of community re-integration, target outcomes reflecting veterans' self-identified problems and self-rated functional competence. Results : At follow-up, VIP participants had significantly higher community re-integration scores and less difficulty managing targeted outcomes, compared to controls. Self-rated functional competence did not differ between groups. In addition, VIP's acceptability was high. Conclusion : A home-based, family-inclusive service for veterans with TBI shows promise for improving meaningful outcomes and warrants further research and clinical application.